Phishing dan Upaya Perlindungan Hukum di Indonesia Sebagai Ancaman Kejahatan Siber - Gina Sonia Kafiar (Lembaga Pengembangan Kinerja Dosen, 2026)
Phishing is a form of cybercrime that has experienced a significant increase in frequency within Indonesia. This fraudulent practice aims to deceive victims into surrendering personal data or sensitive financial information by impersonating trusted institutions. Such crimes result in substantial losses for both individuals and the business sector, particularly concerning personal data protection and digital transaction security. This research aims to analyze the legal regulations and the role of supervisory institutions in addressing phishing threats in Indonesia using a normative legal research method. The legal analysis encompasses the implementation of the Electronic Information and Transactions Law (UU ITE), specifically Article 28, paragraph (1), and the Personal Data Protection Law (UU No. 27 of 2022), which serves as the primary foundation for privacy rights. Furthermore, this study examines the Consumer Protection Law and the Indonesian Criminal Code (KUHP) as enforcement instruments. The strategic roles of the Financial Services Authority (OJK) and Bank Indonesia (BI) are also discussed in the context of risk mitigation within the financial sector. The findings indicate that law enforcement effectiveness is still hindered by low digital literacy, limited forensic technology infrastructure, and jurisdictional challenges in tracking cross-border perpetrators. Consequently, a synergy between regulatory strengthening, international collaboration, and massive public education is required to comprehensively suppress these cybercriminal activities.